Negative pressure wound therapy versus standard wound care for diabetic foot ulcers: a systematic review and meta-analysis of healing and limb outcomes - Chao Niu; Kunpeng Fu; Xiuxiao Chen; Yanyang Wang (Frontiers in Endocrinology, 2026)
Background Diabetic foot ulcers (DFUs) are major diabetes-related complications that often require prolonged wound care, debridement, or limb-salvage surgery. Negative pressure wound therapy (NPWT) is widely used as an adjunct, but its comparative effectiveness remains debated. Objective To meta-analyze the efficacy and safety of NPWT versus standard wound care in adults with DFUs. Methods PubMed/MEDLINE, Cochrane CENTRAL, EMBASE, and Web of Science were searched from January 2000 to January 2025 for randomized, quasi-randomized, or prospective controlled studies. The primary outcome was complete healing; secondary outcomes were time to healing, amputation, wound infection, length of stay, and adverse events. Binary outcomes were pooled with random-effects (REML) models using the Hartung-Knapp adjustment; we report 95% prediction intervals and leave-one-out analyses and graded certainty using GRADE. Results Nineteen studies (2,046 patients) were included. NPWT improved complete healing. Because one large trial was a clear statistical outlier driving heterogeneity (I2 = 83%), the primary healing estimate excludes it: risk ratio (RR) 1.42 (95% CI 1.15-1.74; prediction interval 1.08-1.85; I2 = 33%); the full-set estimate including that trial (RR 1.67, 1.24-2.25, P = 0.004) is reported secondarily. The benefit was robust to leave-one-out analysis (RR 1.42-1.78) and to exclusion of high-risk-of-bias studies. For amputation (5 studies) and wound infection (3 studies), point estimates favored NPWT (RR 0.46 and 0.52) but Hartung-Knapp intervals were wide and crossed 1 (0.18-1.17 and 0.25-1.06); with so few studies these reflect insufficient evidence rather than a demonstrated absence of effect. Time-to-healing data were too incompatible to pool (I2 = 91%) and are summarized narratively. Conclusions NPWT is associated with improved complete wound healing in adults with DFUs; this conclusion rests on the most defensible, outlier-excluded analysis and is robust to conservative adjustment, leave-one-out analysis, and exclusion of high-risk studies. Evidence on amputation and infection is insufficient rather than negative. NPWT may be considered for selected patients with deeper or high-risk DFUs when perfusion is adequate and standard care has been insufficient.